Comprehensive Review of Zakat Accounting System in Afghanistan, Its Challenges and Solution in the Light of Sharia - Khogyani, Sayed Anwar (Digital Repository of Theses, 2024)
This dissertation provided a comprehensive review of the Zakat accounting system in Afghanistan, examining its practices, challenges, and potential solutions within the framework of Sharia law. Zakat, one of the Five Pillars of Islam, plays a crucial role in promoting wealth equity and addressing poverty. However, the implementation of an effective Zakat system in Afghanistan faced numerous obstacles, including a lack of standardized accounting practices, inadequate regulatory frameworks, and socio-economic instability. After diving into a bunch of research and doing some qualitative analysis, this study found some major issues like messy Zakat collection and distribution, corruption, and people just not knowing enough about it. It also looked into how these problems affect Zakat’s ability to tackle poverty and push for social justice. In light of Sharia principles, the dissertation proposed several solutions to enhance the Zakat accounting system in Afghanistan. These included the establishment of a centralized Zakat authority, the adoption of standardized accounting practices, and the implementation of transparent and accountable mechanisms for Zakat collection and distribution. The study also stressed how crucial it is to get the community involved and educated so people feel more confident and on board with the Zakat system. This research really adds to the conversation about Islamic finance and social welfare, giving some solid suggestions for policymakers, religious leaders, and financial institutions on how to make Zakat work better in Afghanistan. What we learned from this study not only sheds light on how Zakat fits into Afghanistan's economy but also points out the changes needed to improve the Zakat accounting system so it can actually help people in the community who need it most. Through these efforts, the dissertation aimed to foster a more equitable and just society, aligned with the ethical imperatives of Islamic finance.